1979
DOI: 10.1212/wnl.29.10.1402
|View full text |Cite
|
Sign up to set email alerts
|

Studies in aging of the brain

Abstract: Alzheimer disease was transmitted in a pattern consistent with an autosomal dominant trait in three families. This brings to 50 the number of such families reported. In one of our families, one patient had histologically confirmed Alzheimer disease, whereas her sister had proved spongiform encephalopathy. Other data suggest a link between familial Alzheimer disease and transmissible dementia. Alzheimer disease is associated with abnormal neurofibrillary structures, Down syndrome, and abnormal numbers of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…During this period AD was studied and its lesions characterized by investigators using traditional clinical [2,3] genetic [4][5][6][7] neurohistochemical [8,9] and ultrastructural [10] approaches, with almost nothing being known about its etiology or pathogenesis beyond some indications that AD was associated with damage to cholinergic pathways [11,12]. It was not until the mid 1980s that it became clear that most cases of senile dementia (i.e.…”
Section: Introduction / Historical Perspectivementioning
confidence: 99%
“…During this period AD was studied and its lesions characterized by investigators using traditional clinical [2,3] genetic [4][5][6][7] neurohistochemical [8,9] and ultrastructural [10] approaches, with almost nothing being known about its etiology or pathogenesis beyond some indications that AD was associated with damage to cholinergic pathways [11,12]. It was not until the mid 1980s that it became clear that most cases of senile dementia (i.e.…”
Section: Introduction / Historical Perspectivementioning
confidence: 99%
“…Family studies show an increased risk of the disease in first-degree relatives [1][2][3][4][5][6][7][8]. In some families, AD occurs in a pattern consistent with the effects of an autosomaldominant gene [9][10][11][12]. Other studies have revealed an increased frequency of Down's syndrome in the families of subjects with AD [4,7] although this is not a consistent finding [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Many families have been described in which cases of Alzheimer's disease (AD) tend to aggregate [9]. With an aging popula tion in the Western World in whom the risk of AD is the highest, and with increased awareness about AD in the general popula tion, family members of a case of AD are frequently asking their physicians about their own risk of getting AD.…”
mentioning
confidence: 99%
“…Although the aggregation of cases of Alz heimer's disease within families has been frequently documented, the majority of cases of AD do not have any other family members affected by the disease [7,9,15,16,30] This question will be addressed by sum marizing different types of data dealing with this topic.…”
mentioning
confidence: 99%